Increased cysteine metabolism in PINK1 models of Parkinson's disease. - Travaglio, M.; Michopoulos, F.; Yu, Y.; Popovic, R.; Foster, E.; Coen, M.; Martins, L.M. (Disease models & mechanisms, 2023)
Parkinson's disease (PD), an age-dependent neurodegenerative disease, is characterised by the selective loss of dopaminergic neurons in the substantia nigra (SN). Mitochondrial dysfunction is a hallmark of PD, and mutations in PINK1, a gene necessary for mitochondrial fitness, cause PD. Drosophila melanogaster flies with pink1 mutations exhibit mitochondrial defects and dopaminergic cell loss and are used as a PD model. To gain an integrated view of the cellular changes caused by defects in the PINK1 pathway of mitochondrial quality control, we combined metabolomics and transcriptomics analysis in pink1-mutant flies with human induced pluripotent stem cell (iPSC)-derived neural precursor cells (NPCs) with a PINK1 mutation. We observed alterations in cysteine metabolism in both the fly and human PD models. Mitochondrial dysfunction in the NPCs resulted in changes in several metabolites that are linked to cysteine synthesis and increased glutathione levels. We conclude that alterations in cysteine metabolism may compensate for increased oxidative stress in PD, revealing a unifying mechanism of early-stage PD pathology that may be targeted for drug development. This article has an associated First Person interview with the first author of the paper.